Peningkatan Hasil Belajar Matematika Pada Pokok Bahasan Garis dan Sudut Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Pada Siswa Kelas VIII-E SMPN 2 Plosoklaten - Sumiyati, Sumiyati (Jurnal Simki Pedagogia, 2023)
Problems in learning mathematics that also occur in SMPN 2 Plosoklaten students based on the average grade VIII E student learning outcomes in the competency material for lines and angles have not been achieved to the maximum of 75%, the specified KKM is 76, so the presentation of learning completeness said not finished. Therefore, in carrying out the teaching and learning process, systematic steps are needed to achieve the predetermined goals, so the researchers used the Numbered Head Together (NHT) learning model. NHT is an informal structure approach in cooperative learning. In this study using the classroom action research method, which is a form of research that is reflective, is the development of learning methods and strategies by carrying out certain actions aimed at improving and enhancing the learning process. Student learning outcomes show an improvement when compared to learning outcomes in cycles 1, 2 and 3, this can be seen from the class average which has increased to 80.54 while the number of students who have completed has increased to 39 people, and the percentage of completeness is 97, 5%. Even though there is still 1 person who has not completed it, the child shows a rapid improvement, so remedial teaching is carried out.